1998
DOI: 10.1590/s0066-782x1998000600007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação comparativa entre valvoplastia percutânea e comissurotomia a céu aberto na estenose mitral

Abstract: Both procedures were safe and showed similar immediate improvement in mitral gradient and functional class. Mitral valve area had a greater increase immediately after commissurotomy, however, there was a significantly greater reduction in the CG after 12 months of follow-up, when compared to balloon valvuloplasty. In both groups, mitral gradient remained reduced and most patients did not change functional class during the follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In our country, Cardoso et al [7] in a prospective, randomized study compared the results of open mitral commissurotomy with the balloon valvuloplasty in 88 patients with rheumatic mitral stenosis, with scores <9. The group submitted to balloon valvuloplasty had an increase in the average mitral valve area of 1.05 ± 0.25 cm² to 2.18 ± 0.40 cm², while the commissurotomy group had an increase of 0.98 ± 0, 21 ± 0.46 cm2 to 2.52 cm².…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our country, Cardoso et al [7] in a prospective, randomized study compared the results of open mitral commissurotomy with the balloon valvuloplasty in 88 patients with rheumatic mitral stenosis, with scores <9. The group submitted to balloon valvuloplasty had an increase in the average mitral valve area of 1.05 ± 0.25 cm² to 2.18 ± 0.40 cm², while the commissurotomy group had an increase of 0.98 ± 0, 21 ± 0.46 cm2 to 2.52 cm².…”
Section: Discussionmentioning
confidence: 99%
“…In our midst, Cardoso et al [7] presented a study comparing open commissurotomy with balloon valvuloplasty, with advantage over the increase in valve area for the group submitted to commissurotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Palacios et al 24 also found higher mortality in the group with higher echocardiographic score. Thus, reported mortality during outcome is null in groups selected with favorable medium term 64,65 , and even long term 17 characteristics. Mortality reached 17 and 18% 21,36 , due to the unfavorable characteristics or when greater follow-up period were observed.…”
mentioning
confidence: 99%